ANALISIS BIAYA SATUAN LAYANAN RAWAT INAP PADA RUMAH SAKIT UMUM DAERAH Dr. HARYOTO LUMAJANG - Ikhwansyah, Doni; Zaky, Achmad (Jurnal Ilmiah Mahasiswa FEB, 2014)
The objectives of this research are to understand the determining methods of inpatient hospital services rates and to analyze the unit costs of inpatient hospital services by the ABC system approach. This study uses qualitative research with case study research approach. As the public service institution (BLU), public hospitals are required to perform the unit cost analysis in determining the rates of its services. ABC system is considered as the quite accurate costing approach and it can minimize the distortion at determining unit cost of the products. According to this study, the components of inpatient hospital services cost consist of administrative costs, consumption costs, costs of laundry, salaries of nurses, cleaning fee, costs of water, electricity costs, building maintenance costs, equipment maintenance costs, buildings depreciation and equipments depreciation. While the cost drivers consist of the number of patients, long of stay, the amount of nurses, and the spacious of rooms. Based on these study, it was found that the management of Dr. Haryato Public Hospital did not perform the unit cost analysis to determine the hospital’s services rates. The unit cost of each of these classes has a considerable margin compared with the hospital rates. The hospital management should consider the application of the ABC system in the calculation of unit costs so that the application can be more accurate rates in accordance with the consumption cost of each class.Key Words:   Unit Costs, Hospital Rates, ABC System